2021
DOI: 10.1007/s11625-020-00896-6
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making for nature’s contributions to people in the Cape Floristic Region: the role of values, rules and knowledge

Abstract: Nature conservation on privately owned land depends on land managers’ decision-making. Interactions between values, rules and knowledge (vrk) underpin decision-making, thus, it is important to understand these interactions to support conservation intentions. We investigated how different sets of vrk determine the decision-making context regarding the management and conservation of renosterveld, a critically endangered ecosystem in the Cape Floristic Region, and how this relates to land managers’ perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 72 publications
5
34
0
Order By: Relevance
“…We found that higher levels of relational values and intrinsic values were linked to a positive attitude towards environmental conservation, as well as more frequent use of local natural goods (Admiraal et al, 2017;Knippenberg et al, 2018;van den Born et al, 2017). This could suggest that people with higher relational values are more likely to support conservation agendas (Mattijssen et al, 2020;Topp et al, 2021). Our results showed that the involvement in environmental conservation groups or projects did not have any significant influence on relational values, suggesting that is it not the active involvement per se that is linked to stronger relational values, but rather that strong relational values underpin a positive perception of conservation.…”
Section: Discussionmentioning
confidence: 79%
“…We found that higher levels of relational values and intrinsic values were linked to a positive attitude towards environmental conservation, as well as more frequent use of local natural goods (Admiraal et al, 2017;Knippenberg et al, 2018;van den Born et al, 2017). This could suggest that people with higher relational values are more likely to support conservation agendas (Mattijssen et al, 2020;Topp et al, 2021). Our results showed that the involvement in environmental conservation groups or projects did not have any significant influence on relational values, suggesting that is it not the active involvement per se that is linked to stronger relational values, but rather that strong relational values underpin a positive perception of conservation.…”
Section: Discussionmentioning
confidence: 79%
“…Our research adds to nascent research literature on the social aspects of private land conservation in South Africa (see e.g. Selinske et al 2015, Gooden & Grenyer 2019, Topp et al 2021) by investigating landowners' willingness to conserve oribi antelope, which are heavily dependent on remnant grassland habitat on private lands and are under considerable pressure from illegal hunting. We found that private landowners were willing to protect oribi on their lands, which is critical to oribi conservation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Chikanda powder is then added to thicken and bind the mixture giving the product a gelatinous texture, similar to that of polony (Kaputo 1996) (Photo: Carolyn Cramer) use economy amongst poorer people, many of whom value these species as part of their cultural heritage, but nevertheless operate at the margins of formal food systems. While much of the TEK around the use of NUS in the Cape Floristic Region is considered lost, recent studies attest to a sustained knowledge base amongst NUS users in different communities across the biodiversity-rich phytoregion, especially amongst residents with generational ties in these areas (de la Fontaine and Malgas 2013;de Vynck et al 2016a;Malgas et al 2018;Tembo-Phiri 2019;Topp et al 2021). By including TEK, it can possibly prevent the further exclusion of the most marginalised members of the local communities (and their local knowledge), instead facilitating equitable ways to connect diverse cohorts of contemporary users and knowledge holders.…”
Section: Knowledge and Equity In Enabling A More Inclusive Food Systemmentioning
confidence: 99%